Predilation Ballooning in High Thrombus Laden STEMIs: An Independent Predictor of Slow Flow in Patients Undergoing Emergent Percutaneous Coronary Revascularization - Imad Uddin, Muhammad Waleed, Shakir Ghaffar, Muhammad Abdur Rauf, Muhammad Ishaq Khan, Muhammad Idrees Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Predilation ballooning in high thrombus-laden ST-elevation myocardial infarctions (STEMIs) is a technique used during emergent percutaneous coronary revascularization (PCI) to improve blood flow and reduce clot burden in the coronary artery. Objectives: The main objective of the study is to find the predilation ballooning in high thrombus laden STEMIs as an independent predictor of slow flow in patients undergoing emergent percutaneous coronary revascularization. Material and methods: The study was a retrospective analysis of 280 consecutive patients who underwent emergent PCI for STEMI at Hayat Abad Medical Complex. Data were collected from electronic medical records of patients who met the inclusion criteria, which were patients with STEMI who underwent emergent PCI and had high thrombus burden as assessed by angiography. Patients who did not undergo predilation ballooning or who had missing data were excluded from the analysis. The collected data included demographics, clinical characteristics, laboratory values, angiographic findings, procedural details, and outcomes. Results: The results of the study show that predilation ballooning is an independent predictor of slow flow in patients undergoing emergent percutaneous coronary revascularization for high thrombus burden STEMI in the sample of 280 patients. Data presents a comparison between two groups of patients who underwent emergent percutaneous coronary revascularization with and without predilation ballooning. The comparison is based on demographic, clinical, and angiographic characteristics, as well as postprocedure in-hospital complications and outcomes. The two groups were propensity-matched in a 1:1 ratio to account for potential confounding factors. Conclusion: In conclusion, our study suggests that predilation ballooning may be an independent predictor of slow flow in patients undergoing emergent percutaneous coronary revascularization. The comparison of demographic, clinical, and angiographic characteristics between the predilation ballooning (+) and predilation ballooning (-) groups did not reveal any significant differences, indicating that the two groups were similar in terms of baseline characteristics.